SAE Technical Paper Series 2015
DOI: 10.4271/2015-24-2441
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of High Injection Pressure on Future Heavy Duty Engine Performance

Abstract: Diesel fuel injection pressures have increased steadily on heavy duty engines over the last twenty years and pressures as high as 300MPa are now possible. This was driven by the need to control toxic exhaust emissions, in particular particulate emissions using advanced in-cylinder combustion strategies. With the introduction of efficient aftertreatment systems for both particulate and NOx emissions control there is less demand for in-cylinder emissions control especially considering the drive for improved fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…This is indicative of good air-diesel fuel mixing, and high air utilisation. A fuel injection pressure of 2000 bar was selected for the current work, based on a previous extensive optimization study [15]. Although lower than the 3000 bar capability of the F2E system, this pressure provided the best result at the A50 condition.…”
Section: Thermal Efficiency and Carbon Emissionsmentioning
confidence: 99%
“…This is indicative of good air-diesel fuel mixing, and high air utilisation. A fuel injection pressure of 2000 bar was selected for the current work, based on a previous extensive optimization study [15]. Although lower than the 3000 bar capability of the F2E system, this pressure provided the best result at the A50 condition.…”
Section: Thermal Efficiency and Carbon Emissionsmentioning
confidence: 99%
“…The latest fuel injection equipment (FIE) can obtain up to 250 MPa injection pressure for light-duty and up-to 300 MPa for heavy-duty compression ignition (CI) engines. 10,11 Effects of higher injection pressure on heavy-duty diesel engines have been studied in detail, [12][13][14] and researchers have also tried to figure out the optimum injector geometry for diesel engines which produces the best combustion characteristics with minimum emissions. 13,15 Some researchers have reported that increasing the injector hole number while decreasing the hole diameter helps in particulate matter (PM) reduction because of better fuel atomization and mixing with air while few others have suggested that increasing injector hole number has an adverse effect on PM-NOx trade-off especially when operating at high load condition.…”
Section: Introductionmentioning
confidence: 99%
“…The higher injection pressure also influences a more uniform atomization of fuel. High injection pressure enhances cavitation formation inside the injection nozzle, which influences a better spray break up process and higher fuel velocity at the nozzle exit [19][20][21]. Fuel spray formation and break up processes are also influenced by the number of injection holes and shape of the nozzle sac volume [22].…”
Section: Modern Internal Combustion Engine Technologiesmentioning
confidence: 99%